Environmental factors modulating the bathymetric distribution of the demographic groups of achelous spinimanus (Crustacea) - Bernardo, Camila Hipolito [UNESP]; Bernardes, Veronica Pereira [UNESP]; Sousa, Aline Nonato de [UNESP]; Rodrigues, Gabriel Fellipe Barros [UNESP]; Silva, Thiago Elias da [UNESP]; Fransozo, Adilson [UNESP] (Pensoft Publishers, 2019)
The spatio-temporal distribution of Achelous spinimanus demographic groups (juveniles, and adult males and females) and its relation with environmental factors was analyzed in the region of Ubatuba, southeastern Brazil. We performed the samplings from January to December 2000, at eight sites of different depths. A total of 402 specimens of A. spinimanus was captured. The lowest abundance of all demographic groups occurred in summer, while in winter and spring the abundance of adults was very high. Spatially, juveniles were found at 5 to 35m of depth, while adults at 15 to 40m, but were more abundant at 25m. The low abundance of all demographic groups during summer is probably due to the arrival of the South Atlantic Central Water in the region, which decreased the water temperature and salinity. These changes caused the migration of A. spinimanus to more sheltered places of the bay, possibly due to more favorable environmental conditions. The high abundance of the demographic groups at 25m of depth was due to its more heterogeneous sediment, and to avoid competition with other species more abundant in shallower areas. Therefore, the factors that modulate the distribution of A. spinimanus may differ depending on the ontogenetic phase.
Fatores ambientais modulando a distribuição batimétrica dos grupos demográficos de Achelous spinimanus (Crustacea)
Keywords: Ecological niche; Interspecific relations; SACW; Seasonal migration